Imputation rules for the implementation of the pre-unification education variable in the BASiD Data Set - Nicole Gürtzgen; André Nolte (Journal for Labour Market Research, 2017)
Using combined data from the German Pension Insurance and the Federal Employment Agency (BASiD), this study proposes different procedures for imputing the pre-unification education variable in the BASiD data. To do so, we exploit information on education-related periods that are creditable for the Pension Insurance. Combining these periods with information on the educational system in the former GDR, we propose three different imputation procedures, which we validate using external GDR census data for selected age groups. A common result from all procedures is that they tend to underpredict (overpredict) the share of high-skilled (low-skilled) for the oldest age groups. Comparing our imputed education variable with information on educational attainment from the Integrated Employment Biographies (IEB) reveals that the best match is obtained for the vocational training degree. Although regressions show that misclassification with respect to IEB information is clearly related to observables, we do not find any systematic pattern across skill groups. – – Wir entwickeln eine neue Methode zur Identifizierung verheirateter Paare in administrativen Daten. Mittels Adressdaten und Nachnamen der Gesamtheit der Beschäftigungsmeldungen in Deutschland, identifizieren wir ca. 3,3 Millionen Paare von Personen die an der gleichen Adresse wohnen, deren Nachnamen übereinstimmen, und einen Altersabstand von weniger als 15 Jahren haben. Wir zeigen mittels verschiedener Konsistenzchecks, dass ca. 89 bis 94 Prozent dieser Paare tatsächlich verheiratete Paare sind. Anhand von Informationen des Mikrozensus, zeigen wir, dass unsere Methode etwa 17 Prozent aller verheirateten Paar in Deutschland identifiziert und ca. 35 Prozent aller Paare bei denen beide Partner in sozialversicherungspflichtiger Beschäftigung oder arbeitslos sind. Der Paarindikator wird der Forschungsgemeinschaft und Nutzern der IAB Daten zur Verfügung gestellt. Unsere Methode eröffnet damit neue Forschungsmöglichkeiten für Haushaltsanalysen die von der Präzision und großen Beobachtungszahlen von administrativen Daten profitieren.
Keywords: I2; C81; 330; Imputation rules; Administrative data; East Germany; Education; Institutions